Climatically forced moisture supply, sediment flux and pedogenesis in Miocene mudflat deposits of south-east Kazakhstan, Central Asia - Voigt, Silke; Bahr, André; Pross, Jörg; Koutsodendris, Andreas (The Depositional Record, 2017)
The continental settings of Central Asia witnessed increased desertification during the Cenozoic as a result of mountain uplift and the Paratethys retreat. The interaction of these tectonic-scale processes with orbitally forced climate change and their influence on Asia's atmospheric moisture distribution are poorly constrained. A Miocene succession of continental mudflat deposits, exposed in the Aktau Mountains (Ili Basin, south-east Kazakhstan), has great potential as a terrestrial palaeoclimate archive. About 90 m of the 1700 m thick succession comprise alluvial mudflat deposits and appear as cyclic alternation of coarse sheet floods, mudflat fines and semi-arid hydromorphic soils. In this study, bulk-sediment mineralogy and geochemistry, magnetic susceptibility, sediment colour and palynology are used to reconstruct environmental conditions by determining changes and forcing mechanisms in the intensity of sediment discharge, weathering and pedogenesis. The results presented here indicate four major periods of arid soil formation and one palustrine interval characterized by higher evaporation rates under highly alkaline/saline conditions. A positive correlation between weathering indices and the Mg/Al ratio suggest that these horizons correspond to maximum rates of evapotranspiration and aridity. The formation of mudflat fines is, instead, interpreted as representing higher detrital sediment production by more intense alluvial fan activity during times of higher precipitation. Time series analysis of weathering indices, colour and magnetic susceptibility data yields cycle-to-frequency ratios with the potential to represent Milankovitch cyclicity with short and long eccentricity as dominant periodicities. Periods of pronounced aridity, paced by long eccentricity forcing, reflect changes in moisture availability. On longer tectonic timescales, the persistent appearance of gypsum indicates a shift towards more arid conditions. This trend in climate is considered to result from the closure of the eastern gateway of the Mediterranean to the Indian Ocean that restricted circulation and enhanced salinity within the Eastern Paratethys.
Gesehen am 14.02.2018